2021
DOI: 10.1101/2021.05.06.442900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heat Shock Factor 1 (HSF1) as a new tethering factor for ESR1 supporting its action in breast cancer

Abstract: Heat shock factor 1 (HSF1), a key regulator of transcriptional responses to proteotoxic stress, was recently linked to estrogen (E2) signaling through ESR1. We found that an HSF1 deficiency could lead to the inhibition of the mitogenic action of E2 in breast cancer cells. The stimulatory effect of E2 on the transcriptome is weaker in HSF1-deficient cells, in part due to the higher basal expression of E2-dependent genes, which correlates with the enhanced binding of unliganded ESR1 to chromatin. HSF1 and ESR1 c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(67 reference statements)
1
0
0
Order By: Relevance
“…It has been confirmed that the HSF1-null isogenic MCF7 clones used in this study are incapable of elevating the transcription of stress-inducible HSPA1 and HSPH1 genes after heat shock insult [31]. Here, we found that the removal of HSF1 has no influence on the basal levels of HSPA1 protein, but it was associated with elevated levels of HSPA2 compared to that of wt and CRISPR-CTL cells (Figure 5e).…”
Section: Hsf1 Contributes To Cytoprotection Against Ma Toxicitysupporting
confidence: 81%
“…It has been confirmed that the HSF1-null isogenic MCF7 clones used in this study are incapable of elevating the transcription of stress-inducible HSPA1 and HSPH1 genes after heat shock insult [31]. Here, we found that the removal of HSF1 has no influence on the basal levels of HSPA1 protein, but it was associated with elevated levels of HSPA2 compared to that of wt and CRISPR-CTL cells (Figure 5e).…”
Section: Hsf1 Contributes To Cytoprotection Against Ma Toxicitysupporting
confidence: 81%